2018
DOI: 10.2989/17280583.2018.1424634
|View full text |Cite
|
Sign up to set email alerts
|

Effects of psycho-education plus basic cognitive behavioural therapy strategies on medication-treated adolescents with depressive disorder in Nigeria

Abstract: This study suggests that adding psycho-education with elements of CBT to antidepressant treatment is feasible, acceptable and can produce further benefits to depressed adolescents in this region.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 16 publications
0
25
0
Order By: Relevance
“…2 ). Studies rated as lower quality (Aubuchon-Endsley & Callahan, 2014 ; Gillig et al, 2019 ; Isa et al, 2018 ; Lin et al, 2013 ; Sælid & Nordahl, 2017 ; Smith et al, 2011 ; Teodorczuk et al, 2019 ) did not appear markedly different in reported interventional effects on hopefulness but reported larger effects on depression. Qualitative studies of lower quality (Anttila et al, 2015 ; Midgley et al, 2016 ; Watsford et al, 2013 ) were those which largely focused on hopes for therapy.…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…2 ). Studies rated as lower quality (Aubuchon-Endsley & Callahan, 2014 ; Gillig et al, 2019 ; Isa et al, 2018 ; Lin et al, 2013 ; Sælid & Nordahl, 2017 ; Smith et al, 2011 ; Teodorczuk et al, 2019 ) did not appear markedly different in reported interventional effects on hopefulness but reported larger effects on depression. Qualitative studies of lower quality (Anttila et al, 2015 ; Midgley et al, 2016 ; Watsford et al, 2013 ) were those which largely focused on hopes for therapy.…”
Section: Resultsmentioning
confidence: 95%
“…The specific psychological interventions identified were incredibly variable (see Online Appendix E), ranging from cognitive and/or behavioral-based therapies (Fowler et al, 2018 ; Gee et al, 2018 ; Isa et al, 2018 ; Lin et al, 2013 , 2014 ; Metsäranta et al, 2019 ; Ritschel et al, 2011 , 2016 ; Sælid & Nordahl, 2017 ; Shepherd et al, 2018 ) to other talking (Conklin, 2009 ; Green et al, 2007 ; Leibovich et al, 2020 ; Teodorczuk et al, 2019 ), arts (Walsh & Minor-Schork, 1997 ) or activity-based (Gabrielsen et al, 2019 ; Gillig et al, 2019 ; Hambridge, 2017 ; Smith et al, 2011 ) interventions. Interventions were variable with respect to duration and number of sessions (Online Appendix E).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the selected studies used various data sources; the majority obtained from patients (n=21), and direct methods were not used in the included studies. As previously mentioned the variation of the prevalence of medication adherence, the rate of adherence as assessed by using self-reported, claims database/refill data, pill count, health provider's report (self-report, patient record) ranged from 10.6% to 81%, 19,[21][22][23]34,[46][47][48][49][50][51][52][53][54][55][56][57][58][59][60][61][62] 10% to 62.9%, 25,34,63-70 45%, 71,72 and 69.2% to 85.4%, 34,58 respectively. The most common included studies utilized standardized and structured data collection tool, and structured interviews to measure adherence.…”
Section: Methods To Assess Medication Adherencementioning
confidence: 99%
“…23 However, race-gender also associations with adherence, AD adherence difference across four race-gender subgroups (African-American women, African-American men, White women, and White men), white women more likely to be adherent to their AD medication 3.1 times than African-American women. 50 Moreover, marital status exhibits significant differences in the level of medication adherence. According to Baeza-Velasco et al 48 reported that high adherent patients have a partner.…”
Section: Factors Affect To Medication Adherencementioning
confidence: 99%